Analisis Peran Kepala Sekolah dalam Implementasi Penilaian Kinerja Guru - Muthi’ah Amelia Nuruddin; Rizki Alifiana Saputri; Farah Fadhilah; Sofi Umi Muslimah; Annafi’ Nurul ‘ilmi Azizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the role of the principal in implementing teacher performance appraisal and its impact on the quality of learning at TK Islam Al-A’raaf Gentan. The research employed a qualitative approach with a descriptive design, in which data were collected through observation, interviews, and documentation. The subjects of this study were the principal and teachers, focusing on the implementation of teacher performance appraisal and its follow-up processes. The findings indicate that the principal plays a strategic role in planning, implementing, and evaluating teacher performance appraisal through systematic academic supervision, including pre-observation, observation, and post-observation stages. The follow-up actions are carried out in a structured manner, ranging from guidance and warnings to rewards for high-performing teachers. The implementation of teacher performance appraisal has a positive impact on the quality of learning, such as improving teacher professionalism, creating active and engaging learning environments, and enhancing students’ motivation and learning outcomes. Therefore, the effective role of the principal in teacher performance appraisal is a crucial factor in improving educational quality.